The Impact of Gender on Entrepreneurial Intention in a Peripheral Region of Europe: A Multigroup Analysis - Gomes, Sofia (2021)
The last two decades were characterized by an increase in attention on entrepreneurship. An emerging trend in the literature is associated with the different contributions that genders may have regarding entrepreneurship and entrepreneurial intentions. This paper assesses gender impact on entrepreneurial intention in a peripheral region of Europe. The methodology used is quantitative and based on a sample of 1114 observations. The obtained results suggest that women’s perceived behavioral control does not have a less direct positive impact on entrepreneurial intention when compared to men’s. Women’s personal attitude has a less direct positive impact on entrepreneurial intention when compared to men’s, as social norms, on the one hand, have a less direct positive impact on women’s personal attitude when compared to men’s, and, on the other hand, have a less direct positive impact on women’s perceived behavioral control when compared to men’s. Finally, it was also verified that social norms have a less positive indirect impact through personal attitude and perceived behavioral control on women’s entrepreneurial intention when compared to men’s. These findings contribute to enlighten the literature by strengthening the theoretical framework on women’s entrepreneurial intention in peripheral regions. Regarding practical contributions, suggestions are addressed to public decision makers, universities, and civil society, to adopt practices to increase entrepreneurship in women. This research is original because it is the first to perform this study in Portugal, a peripheral region of Europe.